Unexpected but unsurprising lineage diversity within the most widespread Neotropical crocodilian genus Caiman (Crocodylia, Alligatoridae). Issue 4 (18th May 2020) - Roberto, Igor J.; Bittencourt, Pedro S.; Muniz, Fabio L.; Hernández-Rangel, Sandra M.; Nóbrega, Yhuri C.; Ávila, Robson W.; Souza, Bruno C.; Alvarez, Gustavo; Miranda-Chumacero, Guido; Campos, Zilca; Farias, Izeni P.; Hrbek, Tomas
Abstract : Species discovery methods utilizing coalescent-based approaches are powerful tools for detecting cryptic lineages within morphological conservative groups, thus being an important methodology of integrative taxonomic research. Crocodilians are a classic example of morphologically conserved group where coalescence-based species delimitation analyses resulted in the discovery of cryptic lineages and potentially new species. In this study, we used several single locus species discovery methods to analyze the phylogenetic diversity of the most widespread alligatorid genus of the Neotropics, the genus Caiman. We analyzed 479 specimens representing all named taxa, with the exception of Caiman crocodilus apaporiensis, and known geographic distribution of these taxa. We observed high lineage diversity within the Caiman crocodilus / yacare complex, ranging from 7 to 10 lineages, and three lineages within Caiman latirostris . We also provide a new dated phylogeny for all the delimited lineages. Oligocene and Miocene events triggered the diversification of the major lineages, with latter Pleistocene events influencing the final diversification of the genus. We demonstrate that the discovered lineages within the Caiman complex are compatible with being species and as such are candidates for an integrated taxonomic analysis. However, it is important to highlight that independent of the future recognition of these lineages as species, it is extremely important to protect these cryptic lineages as unique evolutionary entities, many of which are highly threatened by habitat loss from dam construction projects, tailing dam collapses, mining, agriculture and agricultural run-off across all of South America.